Correlation between peripapillary retinal nerve fiber layer thickness and visual function changes in patients receiving ethambutol (Faculty of Medicine Universitas Indonesia, 2015)
Background: Recent animal studies revealed the decreased amount of retinal ganglion cells after treatment with ethambutol. The aim of this study was to evaluate the changes of peripapillary retinal nerve fiber layer (RNFL) thickness in patients receiving ethambutol therapy, as well as to know the correlation of RNFL thickness changes with the changes of visual function. Methods: This was a cohort study on 29 subjects at one tuberculosis treatment center, Jakarta. Subjects underwent RNFL thickness measurement using optical coherence tomography (OCT) and several visual function parameters (visual acuity, contrast sensitivity, color sensitivity and visual field) before and two-months following ethambutol therapy. Statistical comparison between pre- and post- ethambutol measurements were done using either paired T-test or Wilcoxon test. Correlations between anatomical and functional changes were assessed with Spearman correlation test. Results: There were significant changes of peripapillary RNFL thickness in superior (147 and 141 μm, p = 0.001), nasal (92 and 88 μm, p = 0.045) quadrants and average RNFL thickness (116.77 and 112.65 μm, p = 0.001). No significant correlation between RNFL thickness changes and the changes of visual function parameters (p > 0.05). Conclusion: Ethambutol consumption for two months in recommended dose is still considered safe to human retina and visual status.